Influence of environmentally relevant concentrations of vinclozolin on quality, DNA integrity, and antioxidant responses of sterlet Acipenser ruthenus spermatozoa - Gazo, Ievgeniia; Linhartova, Pavla; Shaliutina, Anna; Hulak, Martin (Chemico-biological interactions, 2013)
The effects of vinclozolin (VIN), an anti-androgenic fungicide, on quality, oxidative stress, DNA integrity, and ATP level of sterlet (Acipenser ruthenus) spermatozoa were investigated in vitro. Fish spermatozoa were incubated with different concentrations of vinclozolin (0.5, 2, 10, 15, 20 and 50 μg/l) for 2 h. A dose-dependent reduction in spermatozoa motility and velocity was observed at concentrations of 2-50 μg/l. A dramatic increase in DNA fragmentation was recorded at concentrations 10 μg/l and above. After 2 h exposure at higher test concentrations (10-50 μg/l), oxidative stress was apparent, as reflected by significantly higher levels of protein and lipid oxidation and significantly greater superoxide dismutase activity. Intracellular ATP content of spermatozoa decreased with increasing concentrations of VIN. The results demonstrated that VIN can induce reactive oxygen species stress in fish spermatozoa, which could impair the sperm quality, DNA integrity, ATP content, and the antioxidant defense system.
Keywords: oxazoly; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Antioxidants; DNA; Sperm Motility; fragmentace DNA; Oxazoles; DNA Fragmentation; mužské pohlaví; Oxidative Stress; chemické látky znečišťující vodu; antioxidancia; Water Pollutants, Chemical; průmyslové fungicidy; zvířata; Fungicides, Industrial; adenosintrifosfát; Environment; motilita spermií; Fishes; životní prostředí; oxidační stres; ryby; Spermatozoa; Adenosine Triphosphate; spermie; Male; Animals